Inferential accuracy in classroom contexts - Schroeder, Zachary J.; Husman, Jenefer; Hodges, Sara D. (Frontiers in Psychology, 2025)
This paper connects two research traditions—social psychology's examination of inferential accuracy, and educational research on teacher cognition and decision-making, in order to consider how teachers attempt to accurately infer their students' thoughts and feelings during instruction. Our aim is to link the social psychological study of inferential accuracy with several prominent educational constructs related to teacher expertise. We begin by introducing inferential accuracy and providing a brief overview of social psychology research about it. We suggest that inferential accuracy may affect teacher decisions in what are known as “discretionary spaces” in classroom settings. Next, we delineate similarities and differences between inferential accuracy and two constructs related to teacher expertise (diagnostic competence and teacher noticing). We then identify the parallels between inferential accuracy and two other educational constructs—pedagogical content knowledge and informal formative assessment. Throughout this synthesis, we consider applications of inferential accuracy research to inform how, and how well, teachers may be able to infer their students' thoughts and feelings during instruction, as well as the ways that social psychology researchers may consider teacher-student classroom interactions as fruitful settings in which to examine interpersonal accuracy. We point out the educational constructs that correspond to social psychological predictors of inferential accuracy, discuss areas of tension when translating inferential accuracy research into educational contexts, and suggest future research questions that may prove fruitful with interdisciplinary collaboration.